A comparison of 3D interest point descriptors with application to airport baggage object detection in complex CT imagery - Flitton, Greg T.; Breckon, Toby P.; Megherbi, Najla (Elsevier, 2013)
We present an experimental comparison of 3D feature descriptors with application to threat detection in Computed Tomography (CT) airport baggage imagery. The detectors range in complexity from a basic local density descriptor, through local region histograms and three-dimensional (3D) extensions to both to the RIFT descriptor and the seminal SIFT feature descriptor. We show that, in the complex CT imagery domain containing a high degree of noise and imaging artefacts, a specific instance object recognition system using simpler descriptors appears to outperform a more complex RIFT/SIFT solution. Recognition rates in excess of 95% are demonstrated with minimal false-positive rates for a set of exemplar 3D objects.
Keywords: CT baggage scan; Threat detection; Object recognition; 3D feature descriptors; CT object SIFT